Enhanced Image Security through 4D Hyperchaotic System and Hybrid Key Techniques - Farandi, Muhammad Naufal Erza; Winarno, Sri; Fauzyah, Zahrah Asri Nur (Sistemasi: Jurnal Sistem Informasi, 2024)
This study develops a digital image encryption method using a 4D hyperchaotic system combined with a hybrid key to maximize data security. By generating a random and uniform pixel distribution, the method makes decryption significantly harder for unauthorized access. Evaluations are conducted through histogram analysis, robustness tests, NPCR, UACI, and information entropy. The findings reveal that the method effectively breaks pixel correlation, rendering the encrypted image unrecognizable. Histogram analysis confirms a uniform pixel distribution, while robustness tests show the system can maintain image quality despite manipulations or attacks. NPCR and UACI tests highlight the method’s high sensitivity to even minor changes in the original image, further enhancing security. Information entropy demonstrates a higher level of randomness compared to other encryption techniques. This 4D hyperchaotic and hybrid key-based approach holds considerable promise for applications requiring highly secure image transmission and storage, ensuring reliable data protection in sensitive environments.